Comparative study on the degradation of cephalexin by four electrochemical advanced oxidation processes: Evolution of oxidation intermediates and antimicrobial activity - Antonin, Vanessa S.; Aquino, Jose M.; Silva, Bianca F. [UNESP]; Silva, Adilson J.; Rocha-Filho, Romeu C. (Elsevier B.V., 2019)
The degradation of the beta-lactam antibiotic cephalexin (CEX) was carried out by the following electrochemical advanced oxidation processes (EAOPs): anodic oxidation (AO), Fered-Fenton (EF-Fered), photoassisted anodic oxidation (PAO), and photoassisted Fered-Fenton (PEF-Fered). All experiments were done in a flow reactor incorporating a boron-doped diamond anode, at a low current density; for the PAO and PEF-Fered processes, the solution was irradiated with UVA light. The initial removal of CEX was attained by all EAOPs, but it was much faster by the Fenton-based processes, which thus presented higher initial rates of TOC removal. However, the coupling of the electrolytic and UVA photolytic processes enhanced the mineralization process; as a consequence, significantly greater TOC removals were attained by the PEF-Fered and PAO processes. From the initial oxidation intermediates detected by LC-MS/MS for the PEF-Fered and AO processes, it could be concluded that addition reactions involving the electrophilic HO center dot radicals occurred preferentially in the beta-lactam ring; however, due to the higher availability of HO center dot radicals, the Fenton-based process led to a faster rupture of that ring. Thus, the antibacterial activity of the treated CEX solution against Escherichia coli was completely terminated within less than 1 h of treatment by the PEF-Fered process, compared to 8 h by the AO process. The PEF-Fered and PAO processes yielded enhanced degradation performances despite mere use of UVA light.
Keywords: Fered-Fenton processes; UVA photolysis; BDD anode; Flow electrolysis; Degradation intermediates